2012
DOI: 10.1111/cas.12039
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological significance of MAML2 gene split in mucoepidermoid carcinoma

Abstract: CRTC1-MAML2 and CRTC3-MAML2 fusions have been associated with favorable clinicopathological features of mucoepidermoid carcinomas. However, the significance of the MAML2 gene split has not been fully clarified. In the present study, 95 mucoepidermoid carcinomas (paraffin-embedded materials) were analyzed for CRTC1-MAML2 and CRTC3-MAML2 fusions by RT-PCR and for the MAML2 gene split by FISH. Quantitative RT-PCR for the CRTC1-MAML2 transcript was performed in selected cases. MLL gene involvement, which has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
67
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(68 citation statements)
references
References 21 publications
1
67
0
Order By: Relevance
“…The protein binds to an extended groove that is formed by the interaction of CBF1, suppressor of Hairless, LAG‐1 with ICN, which could positively regulate the Notch signalling pathway 34, 35. In fact, the translocation of MAML2 could create a fusion oncogene MECT1 / MAML2 , which could be involved in the process of disrupting the normal cell cycle, differentiation and tumour development, exerting an oncogenic role in mucoepidermoid carcinoma 36. Recently, the oncogenic CRCT3 ‐ MAML2 fusion was also identified to be associated with a better survival of patients with mucoepidermoid carcinoma 37.…”
Section: Discussionmentioning
confidence: 99%
“…The protein binds to an extended groove that is formed by the interaction of CBF1, suppressor of Hairless, LAG‐1 with ICN, which could positively regulate the Notch signalling pathway 34, 35. In fact, the translocation of MAML2 could create a fusion oncogene MECT1 / MAML2 , which could be involved in the process of disrupting the normal cell cycle, differentiation and tumour development, exerting an oncogenic role in mucoepidermoid carcinoma 36. Recently, the oncogenic CRCT3 ‐ MAML2 fusion was also identified to be associated with a better survival of patients with mucoepidermoid carcinoma 37.…”
Section: Discussionmentioning
confidence: 99%
“…MAML2 rearrangement is observed in more than half of salivary MEC cases, is specific for salivary MEC, and predicts a favorable prognosis [24][25][26][27]. However, MAML2 by FISH was intact in all three of our cases.…”
Section: Discussionmentioning
confidence: 52%
“…MAML2 is located at 11q21, and its encoding protein is capable of forming a multiprotein complex with NIC-RBPJκ, which is an essential step for the Notch-mediated transcriptional activation (33). The oncogenic role of MAML2 was first described in mucoepidermoid carcinoma, in which translocation of MAML2 in mucoepidermoid carcinoma will create a fusion oncogene mucoepidermoid carcinoma translocated 1 (MECT1)—MAML2 that is involved in disrupting the normal cell cycle, differentiation, and tumor development (34). Clinical investigation also demonstrated that mucoepidermoid carcinoma patients with a positive MECT1–MAML2 fusion and MAML2 gene split had significantly longer OS (34, 35).…”
Section: Discussionmentioning
confidence: 99%
“…The oncogenic role of MAML2 was first described in mucoepidermoid carcinoma, in which translocation of MAML2 in mucoepidermoid carcinoma will create a fusion oncogene mucoepidermoid carcinoma translocated 1 (MECT1)—MAML2 that is involved in disrupting the normal cell cycle, differentiation, and tumor development (34). Clinical investigation also demonstrated that mucoepidermoid carcinoma patients with a positive MECT1–MAML2 fusion and MAML2 gene split had significantly longer OS (34, 35). It was reported that MECT1–MAML2 could bind to and activate both c-jun and c-fos, which are known as proto-oncogenes (36).…”
Section: Discussionmentioning
confidence: 99%